Finite strain variation across the Mahabharat Thrust in central Nepal Himalaya - Chamlagain, Deepak; Hayashi, Daigoro (Journal of Nepal Geological Society, 2007)
This paper deals with the three-dimensional strain across the Mahabharat Thrust (MT) in the Malekhu area in central Nepal. The MT served as a glide plane for the Kathmandu Nappe. Its footwall is made up of phyllites, quartzites, and amphibolites, whereas the hanging wall contains garnetiferous schists, biotite schists, and quartzites with a few lenses of augen gneiss. A three-dimensional strain analysis reveals that Nadai’s amount of strain intensity (€s ) ranges from 0.396 to 0.575 in the footwall indicating an increasing trend towards the proximity of the MT. In contrast, the hanging wall shows an increase in (€ s) magnitude away from the MT and its value varies between 0.556 (at the basal part) and 0.795 (upper part). Microtextures and structures revealed dynamic recrystallisation of the footwall and static recrystallisation of the hanging wall rocks. The shape of three dimensional strain ellipsoids, types of microstructures, and mechanisms of grainscale deformation indicated that the footwall was dominantly affected by simple shear deformation at lower temperatures while the hanging wall suffered from pure shear with minor sub-simple shear deformation at relatively higher temperatures.